Teacher Use of ICT: Challenges and Opportunities - Vrasidas, Charalambos; Pattis, Irineos; Panaou, Petros; Antonaki, Maria; Aravi, Christiana; Avraamidou, Lucy; Theodoridou , Katerina; Zembylas, Michalinos (Proceedings of the International Conference on Networked Learning, 2010)
This paper presents the summary of findings from large-scale evaluations of ICT-related teacher professional development programs run by the Cyprus Ministry of Education and Culture, the Cyprus Pedagogical Institute, and the Centre for the Advancement of Research and Development in Educational Technology (CARDET). More than eleven thousand teachers participated in professional development programs, which focused among others on computer literacy skills, pedagogical knowledge needed for technology integration, infusing technology-based activities in the curriculum, and online learning. In addition to a large-scale survey conducted, twenty-four case studies were developed in order to examine in depth the effectiveness of teacher professional development and the challenges faced by practicing teachers with respect to the integration of Information and Communication Technologies (ICT) in the curricula. This paper discusses findings from the large scale survey and enriches the findings with qualitative data from the ethnographic case studies to illustrate insights on effective practices of ICT integration in Cyprus education. The findings presented in this paper shed light to the complexities of integrating ICT in teaching and learning. The research reported is the first of its kind to be conducted in the Cyprus context. Findings reveal that teachers are willing to integrate technology into their teaching practices. However, even though they realize the benefits of ICT integration, a lot of teachers today seem resistant to integrating technologies and using online learning environments. Data collected and analyzed, illustrate that this is due to several factors, such as lack of time, the ill-structured design of the school curriculum, the lack of infrastructure and tools to better support teachers and learners. In order to aid the endeavors of teachers in integrating technologies, more robust professional development programs as well as appropriate technologies, need to be developed that would continuously provide support in order for teachers to be able to overcome the aforementioned problems and challenges faced when attempting to integrate technology. Moreover, better coordination and organization of the professional development programs is necessary, as well as improvements in the school curriculum, infrastructure upgrades, and availability of software programs and supporting learning materials. During the presentation we will discuss examples from concrete projects (E.g. eLAT, OnlinePD, EUPT3) to illustrate the findings and provide recommendations for successful ICT integration and teacher professional development.